Pengaruh variasi kampuh las tumpul terhadap ketangguhan impak dan kekerasan hasil pengelasan metal inert gas pada aluminium 5083 - Yanuar Burhanuddin; Carlos Purba; Tarkono (Jurnal Teknik Mesin Indonesia, 2023)
A poor selection of welding joints is one cause of damage or fractures in welding. Butt joint is one type of welding joint that has many advantages compared to other types. Because during the welding process, the joint area will be completely filled with filler metal. In addition, the manufacturing process of butt welding joint is easy, so it is widely used in the industrial world. In the welding process, the heat input and the cleanliness of the joint surface area must be considered in order not to cause failure of the welding joint. To determine the value of toughness and hardness, the welded specimens were tested using the impact test and hardness test. This research aims to determine the effect of butt welding joint type half V, single V, and double V on the impact toughness and hardness of the aluminium 5083 specimens MIG welding results. The results showed that the highest hardness value was shown by a single V butt joint with a value of 34.0 HRB and the lowest hardness value was shown by a double V butt joint 27.0 HRB. In the impact test, the highest value was shown by a single V butt joint with a value of 0.0756 Joule/ and the lowest impact value was shown by a double V butt joint with a value of 0.0145 Joule/ .